Using and producing urban political space: Nineteenth-Century Antwerp mayors and city councils and their claim to the town hall square. - Vannieuwenhuyze, Karen (Deutsches Institut für Urbanistik, 2019)
This paper focuses on the political appropriation of the Antwerp town hall square - better known as Great Market - between 1830 and 1914. In historiography town hall squares were usually perceived as symbols of united political communities. It was as if behind the facade of the main municipal building only single-minded urban governments and city administrations operated. However, with the culture wars-tradition within nineteenth century political history in mind, this research assumes that not only between subsequent urban governments, but also within one city council opinions were divided on how to use and transform material urban spaces. With the planting of the Tree of Liberty, the restoration of the sculpture of Virgin Mary in the town hall's facade and the inauguration of the monumental Brabofountain the different nineteenth-century Antwerp city councils attempted, each in their own way, to consolidate their control over the Great Market. The subsequent Catholic and liberal urban governments introduced similar and adapted each other's material symbols. The shifts between Catholic and liberal governing periods provide an excellent framework to investigate how differently and/or similarly the subsequent urban governments integrated this specific urban landscape in their governance activities and political campaigns.
Keywords: Stadtgeschichte; Rathausplatz; Symbolgehalt; Repräsentation; Kommunalpolitik; Lokale Identität